Faktor-Faktor yang Mempengaruhi Tingkat Underpricing Saham pada Perusahaan Non Keuangan yang Melakukan Initial Public Offering di Bursa Efek Indonesia Periode 2014-2018 - Posma Sariguna Johnson Kennedy; Selvia Sitompul; Suzanna Josephine Tobing (Journal of Management and Business Review, 2021)
The phenomenon of underpricing occurs in most of the worlds capital markets, including Indonesia, but with varying degrees. This paper discusses underpricing analysis of the non-financial corporations that underbid prime shares in the Indonesia stock exchange, and aims to prove the underpricing phenomenon of non-finance companies that underpricing the initial public offering by 2014-2018 while studying the factors influencing it. The methodology used to this study is quantitative method, use multiple regression in the calculations. The variable under study is financial leverage, underwriters reputation, and company size. The results of the tests prove that of all three variables, only one variable has no effect on underpricing is financial leverage. The variable reputation of underwriter and company size both have a partial negative effect on underpricing, and simultaneously these three variables effect on underpricing. A good and experienced underwriter reputation guarantees investors about determining the best price for the initial public offering at the time of the IPO (Initial Public Offering). The size of the company is a consideration for investors to invest in a company by using the amount of its total assets as a basis for making investment decisions